Fourier Ptychography-Based Measurement of Beam Divergence Angle for Vertical Cavity Surface-Emitting Laser - Leilei Jia; Xin Qian; Lingyu Ai (Photonics, 2023)
The Vertical Cavity Surface-Emitting Laser (VCSEL) has led to the rapid development of advanced fields such as communication, optical sensing, smart cars, and more. The accurate testing of VCSEL beam quality is an important prerequisite for its effective application. In this paper, a method for measuring the divergence angle of the VCSEL far field spot based on transmissive Fourier ptychography is proposed. First, a single CCD multi-angle VCSEL far-field spot acquisition system is designed. Second, based on the proposed Fourier ptychographic algorithm with synchronous optimization of embedded optical transfer function, a resolution-enhanced phase image of the spot is reconstructed and the boundary extracted by the Sobel operator of the phase image is defined as the boundary position of the beam waist. In this way, the beam waist radius of the laser beam is calculated. Finally, the divergence angle of the laser beam is measured via the radius of the beam waist. Compared with the traditional Gaussian beam definition method, the method proposed in this paper has higher accuracy in divergence angle measurement. The experimental results show that this method can improve the divergence angle measurement accuracy by up to 9.7%.